2000
DOI: 10.1002/1522-2683(20000601)21:11<2209::aid-elps2209>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation as a widespread phenomenon in two-dimensional polyacrylamide gel electrophoresis of human blood plasma proteins

Abstract: The human plasma protein patterns obtained by two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) is a good model system for post-translational modifications because of the existence of several "ladders" of protein spots [Anderson, N. L., Anderson, N. G., Electrophoresis 1991, 12, 883-906], so-called "trains" of spots. Our investigation of several proteins, amongst others beta2-microglobulin and the haptoglobin chains, found the differences in isoelectric points (p/) to be due to deamidation of aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…The most abundant fragment detected on two-dimensional gels, with an apparent molecular mass of 28 kDa, represented large parts of the globular NC4 domain. The presence of the 28-kDa fragment in spots on the two-dimensional gel over a large interval of isoelectric points might be due to deamidation of asparagine residues (45). Indeed one of the peptides sequenced appeared to exhibit deamidation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant fragment detected on two-dimensional gels, with an apparent molecular mass of 28 kDa, represented large parts of the globular NC4 domain. The presence of the 28-kDa fragment in spots on the two-dimensional gel over a large interval of isoelectric points might be due to deamidation of asparagine residues (45). Indeed one of the peptides sequenced appeared to exhibit deamidation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…White et al however, showed both non-deamidated and deamidated forms, suggesting that the modification was not related to sample processing. In addition, it has also been suggested that deamidation at Asn-Gly and Asn-Ser motifs are biologically relevant [161,162], which corresponds with the observed deamidation to a B-crystalline (Asn 146 -Gly 147 ) [160] and may explain the proteolysis of MLC-2 between Asn 13 and Ser 14 [88]. Whilst it appears that myofilament and cytosolic proteins are deamidated and preferentially degraded with I/R injury, the role of deamidation in the mitochondria during pathology has not yet been determined.…”
Section: Mitochondrial Signalingmentioning
confidence: 97%
“…Therefore, it seems likely that factors other than N-glycosylation may be modifying the theoretical pI of PSA (7.26), such as changes in the primary sequence or different posttranslational modifications (PTM). Deamidation of asparagines or glutamines have been suggested as modifications responsible for the spot trains of some serum proteins obtained in a 2-DE gel (Sarioglu et al, 2000). The deamidation process generates negatively charged aspartic and glutamic acid residues, which can modify a protein's pI.…”
Section: Characterization Of Psa 2-de Subformsmentioning
confidence: 99%